The Art of Editing; The Importance of Mechanics in Journalistic Writing: A Study of Reporters and Editors; Trade Show Marketlng Idea Kit: A Hands-On Approach for Trade Show Marketers; Seeing is Remembering: How Visuals Contribute to Learning from Television News - Kurt R. Knebusch; Richard P. Carlson (Journal of Applied Communications, 1991)
Review of "The Art of Editing ," by Peter Jacobi in Folio ; "The Importance of Mechanics in Journalistic Writing: A Study of Reporters and Editors," by Steven A. Ward and Rick Seifert ; "Trade Show Marketlng Idea Kit: A Hands-On Approach for Trade Show Marketers", Skyline Displays, Inc.; "Seeing is Remembering: How Visuals Contribute to Learning from Television News," by Doris A. Graber.